Lietuviškas kalbomokslis (1897) by Kazimieras Jaunius: Copies in Lithuanian Memory Institutions - Venckienė, Jurgita (Knygotyra, 2025)
In the last decade of the 19th century, as the national consciousness was growing, the need for grammars of the Lithuanian language increased. Students, who were a particularly active group in society at the time, took it upon themselves to meet this need. Povilas Jakubėnas, Pranciškus Vanagas and Romualdas Žakevičius, who were studying in Dorpat (now Tartu, Estonia), hectographed Lietùviškas Kalbomõkslis (Lithuanian Grammar), a conspectus of the lectures on the Lithuanian language by Kazimieras Jaunius, which were delivered at the Samogitian (Telšiai) Priest Seminary (based in Kaunas) in 1885–1892. Under the conditions of the ban of Lithuanian press in Latin characters, hectograph became a favoured way of publishing.The object of this research is the surviving copies of the hectographed Lietuviškas kalbomokslis by Kazimieras Jaunius. There are several goals: to clarify the history of the hectographing of this work, to identify and describe the surviving copies, and to assess their functioning in the late 19th century and early 20th century. To achieve these goals, first of all, the surviving copies were examined de visu, their condition and binding were assessed, and a comparative analysis was performed. In order to research the functioning of Lietuviškas kalbomokslis, the provenances of the copies were determined, and the manuscript notes, corrections, and other marks left by readers were analysed. Their analysis allows us to assess the dissemination and significance of this work at the end of the 19th century, during the period of the formation of Standard Lithuanian. In addition, the errors noted by readers could be useful in search for the unidentified protograph of Lietuviškas kalbomokslis – i.e., the manuscript conspectus that was hectographed.
Keywords: late 19th century; Kazimieras Jaunius; Povilas Jakubėnas; Pranciškus Vanagas; Romualdas Žakevičius; grammar of the Lithuanian language; hectograph publication; ban of the Lithuanian press